2012
DOI: 10.1177/1073191112444920
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Dutch Brief Form of the Multidimensional Personality Questionnaire (MPQ-BF-NL)

Abstract: This study describes the development and psychometric properties of the Dutch brief form of the Multidimensional Personality Questionnaire (MPQ-BF-NL). Representative samples from the Netherlands (N = 1,055) and the United States (N = 1,153) and a Dutch student sample (N = 987) were used for development, cross- and external validation, respectively. The authors' strategy for item selection and scale validation replicated the development of the U.S. brief form (MPQ-BF). Internal consistencies were generally goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…This is a general self‐report measure of personality, measuring a range of discrete trait dispositions (Patrick, Curtin, & Tellegen, ; see Eigenhuis, Kamphuis, & Noordhof, , for the Dutch version). In this study, two measurements for inconsistent response patterns were used: the Variable Response Inconsistency scale (VRIN) and the True Response Inconsistency (TRIN).…”
Section: Methodsmentioning
confidence: 99%
“…This is a general self‐report measure of personality, measuring a range of discrete trait dispositions (Patrick, Curtin, & Tellegen, ; see Eigenhuis, Kamphuis, & Noordhof, , for the Dutch version). In this study, two measurements for inconsistent response patterns were used: the Variable Response Inconsistency scale (VRIN) and the True Response Inconsistency (TRIN).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, all four factors of the ESEM MPQ-BF model were reasonably well defined, thereby supporting the four-factor oblique ESEM model at the scale-level. Previous PCA/ EFA studies involving the MPQ-BF at the scales level have shown that although the primary factor scales loaded saliently on their target higher-order broad factors, there was considerable crossloadings on the higher-order broad factors [4,8], thereby indicating that the higher-order broad factors in the MPQ-BF were not clearly defined. A likely explanation for the differences in the present study and that of previous studies is that unlike previous studies that used PCA and EFA…”
Section: Mpq Factor Structurementioning
confidence: 92%
“…Absorption loaded on both the higher-order dimensions of Positive Emotionality and Negative Emotionality. In a subsequent study, Eigenhuis, Kamphuis, and Noordhof [8] examined the factor structure of the primary trait scales of the MPQ-BF using EFA. As in Patrick et al's study, the primary trait scales loaded saliently on their target higher-order dimensions.…”
Section: Tellegen's Personality Modelmentioning
confidence: 99%
See 2 more Smart Citations